(6S)-6-fluoroshikimic acid, an antibacterial agent acting on the aromatic biosynthetic pathway. - Davies, G M (1994)
(6S)-6-Fluoroshikimic acid inhibited the growth of Escherichia coli B on minimal medium (MIC, 0.25 micrograms ml-1), and it protected mice challenged intraperitoneally with the same organism (50% protective dose, 0.06 mg kg of body weight-1). We propose that inhibitors of bacterial aromatic biosynthesis have the potential for use in human medicine.